Global Economic Trends: A Study of Data from the Years 1961–2013 - Kyrylych, Volodymyr; Shparyk, Khrystyna (Historia i Polityka, 2019)
This research focuses on the problem of unequal development of the world economy. Manifestations of some modern global economic inequality are evaluated. Relative frequency and statistical characteristics for countries of the world in terms of GDP per capita from 1961 to 2013 are analyzed on which deep divergences between countries and very low average value of GDP per capita are identified. Analysis of quantitative and percentage distribution of countries of the world by the revenue categories shows that lately the inequality between countries has slightly decreased, although it remains to be deep.